High society - Kalla, Daniel (Simon & Schuster Canada, 2024)
"At sixteen, Holly Danvers barely survived the car accident that killed her father. While she has no memory of the crash, it took an ayahuasca treatment, a native plant-based psychedelic therapy, in the jungles of Peru for her to emotionally recover. Twenty years later, Holly is a sought-after psychiatrist determined to use her expertise with psychedelics to treat patients suffering from addictions. Ignoring the risks, she embarks upon an unproven new protocol with miraculous results. But her success in probing the traumas of her patients and the secrets they keep is short-lived. When one celebrity client goes public with his recovery and another overdoses after accusing Holly of improprieties, her world is turned upside down. With her career on the line, Holly reaches out to her mentor—and estranged husband—Dr. Aaron Laing, for advice and comfort. But he has a different agenda, and it soon becomes clear that it will be up to Holly alone to figure out why her clients are relapsing and dying. To accomplish that, she will have to risk her life and revisit her own deep-seated trauma."--